Minimum acceptable diet and its predictors among children aged 6‐23 months in Ethiopia. A multilevel cloglog regression analysis - Tegene Atamenta kitaw; Befkad Derese Tilahun; Biruk Beletew Abate; Ribka Nigatu Haile (Wiley, 2024)
Abstract Despite significant progress made previously and the recognized health benefits of optimal feeding practices, ensuring a minimum acceptable diet in developing countries like Ethiopia remains a formidable challenge. Additionally, there is a scarcity of data in this area. Therefore, our study aims to identify predictors of a minimum acceptable diet using a powerful tool called complementary log‐log regression analysis. Thus, it contributes to accelerating the pathway of ending child undernutrition thereby promoting optimal child health. A multilevel analysis was conducted among a weighted sample of 1427 children aged 6‐23 months using the 2019 Ethiopian Demographic Health Survey (EDHS). The EDHS sample was stratified and selected in two stages. A minimum acceptable diet is defined as a composite of children fed with both minimum dietary diversity and minimum meal frequency. Data extraction took place between August 1 and 30, 2023. We used STATA software version 17 for data analysis. A complementary log‐log regression model was fitted to identify significant predictors of the minimum acceptable diet. A p‐value of ≤0.05 was used to declare statistically significant predictors. Only 10.44% (95CI: 8.90‐12.15) of the children meet the minimum acceptable diet. Child aged (18‐23 month) (AOR = 1.78, 95CI:1.14‐2.78)], mother's educational level (secondary and above education) (AOR = 279,95CI: 1.51‐5.15), number of children three and above [(AOR = 0.78,95CI: 0.53‐0.94], institutional delivery [AOR = 1.77,95CI: 1.11‐3.11], having postnatal‐check‐up [AOR = 2.33,95CI: 1.59‐3.41] and high community poverty level (AOR = 0.49,95CI: 0.29‐0.85) were found to be predictors of minimum acceptable diet. In Ethiopia, only one in ten children achieve a minimum acceptable diet. Which is lower than the global report findings (16%). Enhancing maternal education programs and promoting family planning strategies to reduce household size are essential. Besides, encouraging institutional deliveries and postnatal check‐ups are also recommended. It is necessary to implement targeted interventions for poverty reduction in communities to ensure that families can afford nutritious diets for their children.